2016
DOI: 10.1098/rspb.2015.2263
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced social behaviours inPristionchus pacificushave a distinct evolutionary history and genetic regulation fromCaenorhabditis elegans

Abstract: Wild isolates of the nematode Caenorhabditis elegans perform social behaviours, namely clumping and bordering, to avoid hyperoxia under laboratory conditions. In contrast, the laboratory reference strain N2 has acquired a solitary behaviour in the laboratory, related to a gain-of-function variant in the neuropeptide Y-like receptor NPR-1. Here, we study the evolution and natural variation of clumping and bordering behaviours in Pristionchus pacificus nematodes in a natural context, using strains collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 29 publications
0
69
2
Order By: Relevance
“…Studies on La R eunion Island in the Indian Ocean revealed that P. pacificus has invaded this island multiple times independently with different carrier beetles, resulting in this island harboring the complete worldwide diversity of P. pacificus haplotypes (Herrmann et al, 2010;Morgan et al, 2012). Indeed, the population structure and evolutionary history of P. pacificus on La R eunion Island provided a paradigm for detailed studies of the nematodesadaptations to new environments 2014;2016;Morgan et al, 2014;Moreno et al, 2016). Among several P. pacificus hosts on La R eunion, the endemic rhinoceros beetle Oryctes borbonicus represents an interesting study system because more than 90% of beetle individuals harbor P. pacificus dauer larvae (Morgan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on La R eunion Island in the Indian Ocean revealed that P. pacificus has invaded this island multiple times independently with different carrier beetles, resulting in this island harboring the complete worldwide diversity of P. pacificus haplotypes (Herrmann et al, 2010;Morgan et al, 2012). Indeed, the population structure and evolutionary history of P. pacificus on La R eunion Island provided a paradigm for detailed studies of the nematodesadaptations to new environments 2014;2016;Morgan et al, 2014;Moreno et al, 2016). Among several P. pacificus hosts on La R eunion, the endemic rhinoceros beetle Oryctes borbonicus represents an interesting study system because more than 90% of beetle individuals harbor P. pacificus dauer larvae (Morgan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We propose that a heuristic variant calling procedure simultaenously taking into account the mutant and the wildtype sample is enough to define more reliable sets of candidate mutations. b) The strain RSB001 shows a so called bordering behaviour, which has also been observed in C. elegans but has a different genetic basis [18]. c) A single wildtype worm of P. pacificus .…”
Section: Introductionmentioning
confidence: 92%
“…Based on world-wild field trips to sample more nematode strains, we have recently discovered one P. pacificus strain, RSB001, on a high altitude location on la Reunion Island in the Indian Ocean that shows a so called bordering behaviour ( Fig. 1a,b) that has also been observed in C. elegans [17] but is not controlled by the same gene [18]. Whole genome resequencing data has shown that this and other strains of the same genetic lineage are roughly 1% divergent from the standard P. pacificus reference strain PS312 (isolated in California, USA) [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, strains of another free‐living nematode species, Pristionchus pacificus, which is only distantly related to C. elegans , also display oxygen‐induced social behaviour. However, this behaviour is not regulated by npr‐1 …”
Section: Nematodesmentioning
confidence: 99%